2020
DOI: 10.1007/s11051-020-05041-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A deep learning model and machine learning methods for the classification of potential coronavirus treatments on a single human cell

Abstract: Coronavirus pandemic is burdening healthcare systems around the world to the full capacity they can accommodate. There is an overwhelming need to find a treatment for this virus as early as possible. Computer algorithms and deep learning can participate positively by finding a potential treatment for SARS-CoV-2. In this paper, a deep learning model and machine learning methods for the classification of potential coronavirus treatments on a single human cell will be presented. The dataset selected in this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Khalifa et al [ 40 ] developed a classification approach for the treatment purposes of coronavirus on a single human cell-based on treatment type and treatment concentration level using deep learning and machine learning (ML) methods. Numerical features of the data sets were converted to images for building the DCNN model.…”
Section: Related Literaturementioning
confidence: 99%
“…Khalifa et al [ 40 ] developed a classification approach for the treatment purposes of coronavirus on a single human cell-based on treatment type and treatment concentration level using deep learning and machine learning (ML) methods. Numerical features of the data sets were converted to images for building the DCNN model.…”
Section: Related Literaturementioning
confidence: 99%
“…The conventional machine learning (ensemble) algorithm attained 98.5 percent in study precision in the calculation of treatment concentration level, whereas the projected DCNN method attained 98.2 percent. The performance metrics affirm the accuracy of the outcomes obtained from the research carried out in the classification of therapy and the prediction level of treatment focus [ 32 ]. Utilizing traditional and ensemble machine learning algorithms, it has been suggested to divide documented medical reports into 4 categories.…”
Section: Literature Reviewsmentioning
confidence: 80%
“…In order to show the probability of machine learning for impending investigation, the article provides an initial benchmarking [ 36 ]. In author [ 32 ], they concentrate on current advances in the expansion of artificial intelligence-based COVID-19 medications and inoculations and the ability for smart training to determine COVID-19 infected individual. To promote deep learning applications for SARS-COV-2, several molecular targets of COVID-19, whose inhibition can improve patient survival, are illuminated.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The drugs identified in this research are similar to the drugs identified by Recursion in their study [5] and by the study reported in [17], as all resulted in GS-441524 and Remdesivir being isolated as clear outliers in our probability scores and also their efficacy scores. Notably, our CX-4945 probability score is much more noticeable for the same compound, although all results share the same four most effective drugs, albeit in different rankings and orders of magnitude [28]. Of the identified compounds, CX-4945 and Aloxistatin have entered the observational clinical pretrial phase, while Remdesivir (and by association GS-441524) has been approved by the FDA as the first treatment for COVID-19.…”
Section: Experimental Studymentioning
confidence: 81%